2017
DOI: 10.1080/00952990.2017.1359617
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among bi/multiracial youth in the United States: Profiles of psychosocial risk and protection

Abstract: While bi/multiracial youth in general exhibit elevated levels of substance use, substantial heterogeneity exists among this rapidly-growing demographic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
2
20
0
2
Order By: Relevance
“…Research among multiracial adolescents is important because findings from monoracial adolescents may not apply to adolescents with complex racial identities and distinct experiences ( Shih and Sanchez 2009 ). Moreover, there is mounting evidence that multiracial adolescents may be at greater risk than their monoracial peers for health outcomes, including sleep problems ( Udry et al 2003 ) and alcohol use ( Goings et al 2018 ). Despite known associations of sleep problems and alcohol use by which both are reciprocally exacerbated over time ( Koob and Colrain 2019 ), mechanisms underlying these heightened risk behaviors among multiracial adolescents remain a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research among multiracial adolescents is important because findings from monoracial adolescents may not apply to adolescents with complex racial identities and distinct experiences ( Shih and Sanchez 2009 ). Moreover, there is mounting evidence that multiracial adolescents may be at greater risk than their monoracial peers for health outcomes, including sleep problems ( Udry et al 2003 ) and alcohol use ( Goings et al 2018 ). Despite known associations of sleep problems and alcohol use by which both are reciprocally exacerbated over time ( Koob and Colrain 2019 ), mechanisms underlying these heightened risk behaviors among multiracial adolescents remain a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, 5.5 million U.S. adolescents ages 12–17 reported past-year drinking ( Substance Abuse and Mental Health Services Administration 2018 ). In particular, multiracial adolescents may be at greater risk for alcohol use ( Goings et al 2018 ), compared to minority monoracial peers. A nationally-representative study of U.S. adolescents (National Survey on Drug Use and Health [NSDUH]) demonstrated that multiracial adolescents (4% of sample) were more likely to use alcohol compared to their minority monoracial peers (e.g., Black adolescents), but use less than White peers ( Goings et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A família é considerada estratégica para a proteção e socialização de seus membros e para a transmissão dos valores sociais e culturais, além de exercer influência significativa sobre as crenças daqueles, por meio de atitudes e comportamentos relacionados ao processo saúde-doença para lidar com hábitos considerados não saudáveis no contexto familiar, como o abuso de drogas (1,4) .…”
Section: Introductionunclassified
“…Sobre as repercussões das drogas de abuso na família, a experiência dos familiares afetados pode ser devastadora nos aspectos psicológico, financeiro, social e interpessoal do funcionamento familiar. O uso de drogas por um membro da família causa grande pressão sobre o restante dos membros, o que ocasiona dificuldades para se lidar com o problema familiar e com conflitos relacionados ao uso de drogas (2)(3)(4)7) . O impacto do uso de drogas na família se dá por meio de sentimentos negativos como tensão, estresse, preocupação, estigma, raiva e culpa (2,3,7) , entretanto perseverança, coragem, otimismo e esperança são essenciais para se resistir às dificuldades acrescidas no cotidiano familiar (3,6) .…”
Section: Introductionunclassified
“…For example, the National Epidemiologic Survey on Alcohol and Related Conditions survey allows respondents to select multiple racial identities, but recodes responses into a single racial category, thus obfuscating potential racial group differences among Multiracial people (Chen et al, 2016). Yet, some evidence suggests Multiracial people demonstrate higher rates of alcohol use compared to other racial groups (Chavez & Sanchez, 2010;Chen et al, 2012;Goings et al, 2018;Jackson & LeCroy, 2009). For example, Multiracial Native Hawaiians, other Pacific Islanders, and Asian Americans reported higher lifetime alcohol use than their respective monoracial groups (Sakai et al, 2010).…”
mentioning
confidence: 99%